Comparison of soft-tissue and bone surgeries in the treatment of developmental dysplasia of the hip in 18-24-month-old patients - Bulut, Mehmet; Karakurt, Lokman; Azboy, Ibrahim; Demirtas, Abdullah; Ersoz, Galip; Belhan, Oktay (Lippincott Williams & Wilkins, 2013)
The aim of this study was to compare soft-tissue and bone surgeries in 18-24-month-old patients with developmental dysplasia of the hip (DDH). A total of 77 hips of 53 patients were analyzed. Soft-tissue surgery was performed in 31 hips of 25 patients. In the final examination, 23 hips, excluding hips of eight patients who underwent secondary bone surgery, were evaluated (group I). Bone surgery was performed on 46 hips of 28 patients (group II). In group I, the acetabular index was 41 degrees preoperatively and was 20.4 degrees in the final examinations. In group II, the acetabular index was 42 degrees preoperatively and was 15 degrees in the final examinations. To avoid unnecessary surgeries and complications, soft-tissue surgery should be preferred for DDH in 18-24-month-old patients.
Keywords: bone surgery; developmental hip dysplasia; soft tissue; treatment; 18-24 months